Study on fluorination and hydrogenation in transparent conducting zinc oxide thin films - Pham, Anh Tuan Thanh; Nguyen, Phuong Thi; Phan, Thang Bach; Tran, Vinh Cao (Vietnam Journal of Science and Technology, 2020)
Fluorination and hydrogenation are known as two methods for enhancing crystalline structural and electrical properties of ZnO material. The ZnO thin films normally require a low resistivity and a high transmittance for using as high-performance transparent electrodes in optoelectronic applications. In this study, we report successful preparation of fluorinated and hydrogenated ZnO thin films (FZO and HFZO) by using d.c. magnetron sputtering technique. The hydrogenation was carried out by depositing the films in hydrogen plasma atmosphere, while a highly-sintered body of ZnO and ZnF2 compound was employed as a sputtering target for the fluorination. The results show that the strong improvements in carrier concentration, mobility and resistivity of the FZO and HFZO films as compared to the pure ZnO films. The carrier concentration increases to 2x1020 cm-3 which is mainly due to the hydrogenation. The effect combination of the fluorination and the hydrogenation is responsibility for enhancing the mobility up to 43 cm2/Vs. These results give rise to two-order reduction in resistivity, from 0.06 Ohm.cm (ZnO) to 7.5x10-4 Ohm.cm (HFZO), which can be a good choice for thin-film electrode application. In addition, the crystalline structure and optical transmission of the films are also discussed.